Exhaustion of racing sperm in nature-mimicking microfluidic channels during sorting - Tasoglu, Savas (2013)
Fertilization is central to the survival and propagation of a species, however, the precise mechanisms that regulate the sperm's journey to the egg are not well understood. In nature, the sperm has to swim through the cervical mucus, akin to a microfluidic channel. Inspired by this, a simple, cost-effective microfluidic channel is designed on the same scale. The experimental results are supported by a computational model incorporating the exhaustion time of sperm.